Problems of Criminal Applications Law in The Life of Indonesian Communities and Cultures - Rohayu Harun, Rina; Sahid, Mualimin Mochammad; Yamin, Bahri (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
Early January 2023, the President of the Republic of Indonesia ratified the R-KUHP to become Law Number 1 of 2023 concerning the Criminal Code. The new Criminal Code will be enforced in three years, with the agenda of socializing it to all law enforcement officials, and also to all Indonesian people. This study wants to explore the use of the Criminal Code with the various problems that accompany it, during an independent nation. The enactment of the Criminal Code raises its own problems for Indonesian religious people based on the first precepts of Pancasila and having an eastern culture. The method used in this research is doctrinal research or normative legal research and is supported by empirical legal research. The novelty of this study is an analysis of the problems with the application of the Criminal Code so far to strengthen the enforceability of the new Criminal Code which will be implemented in the next three years. Research results are, the problem with the application of the Criminal Code as a form of material criminal law has an impact on all aspects. First, the aspect of legal education where knowledge about criminal law reform is not beneficial due to the maintenance of the Criminal Code, from the judicial or law enforcement aspect, the Criminal Code also continues to be used and even becomes the basis for considering the general rules of Book I of the Criminal Code, as long as it is not regulated in laws and regulations outside the Criminal Code. The validity of the Criminal Code from the perspective of religious law and customary law has gaps that cause problems, such as the adultery article in the Criminal Code which has different meanings and principles from those stipulated in religious law and customary law. The principle of “no excuse”, which is implied in the Criminal Code, does not reflect the religious and cultural character of the Indonesian people by prioritizing the concept of forgiveness.